Effect of Suryanamaskar Practices with and Without Yoga Nidra On Stress Among High School Students- A Randomized Controlled Trial: Life Sciences-Health - Jaiganesh, Dr. K.; Parthasarathy, Dr. S.; Mr. Duraisamy (International Journal of Life Science and Pharma Research, 2022)
Stress is the dynamic connection that exists between an individual and environment where a stimulus (whatever it is) disrupts a person’s homeostasis, causing him or her to react to the circumstances with all resources available. The purpose of this study was to determine the effect of suryanamaskar practises with and without yoganidra on stress levels in high school students. It was hypothesised that the influences of suryanamaskar practises with and without yoga nidra would cause significant differences in stress levels among high school students. To achieve the study’s goal, 45 high school students from various schools near Kandigai, Chennai, with ages ranging from 12 to 15 years old, were chosen and divided into two experimental and control groups of 15 students each. Suryanamaskar practices with yoga nidra were performed by Experimental Group I, and Suryanamaskar practices without yoga nidra were performed by Experimental Group II for a period of 6 weeks, for an hour in the morning. The control group was not exposed to any specific training but they participated in the regular activities. Before and after the training, three groups were given pre- and post-tests. The Everly and Girnando Questionnaire was used to assess stress. The data collected from the three groups prior to and after the training period were statistically analysed using Analysis of Covariance (ANCOVA) to determine the significant difference and tested at the 0.05 level of significance. The study’s findings revealed that suryanamaskar with and without yoga nidra reduced stress significantly. Suryanamaskar combined with Yoga Nidra is more effective than Surya namaskar alone.